PID Based Bean Dryer Temperature Control System Using PLC M580 And Control Valve at PT. Mars Indonesia - Muh Zidane Verianza; Enjelisah; Lutfi; Asyraful Insan Asry (JEAT : Journal of Electrical Automation Technology, 2025)
This study aims to design and implement a PID-based temperature control system for a bean dryer using a Modicon M580 PLC and three separate control valves for each drying zone. This system replaces the previous method, which used only one control valve for all zones. Testing results showed that the average temperature control accuracy in Zone 1 was 93.77%, Zone 2 was 99.12%, and Zone 3 was 91.26%. After installing three control valves, the system's accuracy improved in each zone, with accuracy increases of 4.1% in Zone 1, 5.7% in Zone 2, and 2.8% in Zone 3 compared to the previous setup. These results indicate that the system significantly enhances temperature stability and improves the efficiency of the cocoa bean drying process.